Information literacy in the context of student activism - Kos, Denis (Array, 2014)
This paper discusses the role of information literacy (IL) in the context of student activism and is based on research taken on the sample of students from the Faculty of Humanities and Social Sciences, University of Zagreb, Croatia. The research was a part of two bachelor's thesis which aimed to explore if students recognize and apply modern concepts and competencies which include IL. In a broad sense we aim to define civic participation as a new IL landscape. In the context of making the decision to participate in organized forms of student dissent, this paper aims to examine student opinions, attitudes and behaviour that allow us to define the overall attitude of students towards information and information literacy. Data was collected from June to August, 2012 on the sample of 830 students. The results show that most students are able to locate information in a particular information landscape but their information literacy skills vary depending on how many criteria we use to define information literacy (locating, defining the information need, evaluation, use of information, etc.). Students from the Department of information and communication sciences show higher levels of IL to a certain degree, but these advantages are not present in a continuum, nor can we follow them progress through the comprised years of study. Still, information science students demonstrate a slightly better theoretical understanding of the concept of information literacy.